The structure and dynamics of secretory component and its interactions with polymeric immunoglobulins - Stadtmueller, Beth M; Huey-Tubman, Kathryn E; López, Carlos J; Yang, Zhongyu; Hubbell, Wayne L; Bjorkman, Pamela J (eLife, 2016)
As a first-line vertebrate immune defense, the polymeric immunoglobulin receptor (pIgR) transports polymeric IgA and IgM across epithelia to mucosal secretions, where the cleaved ectodomain (secretory component; SC) becomes a component of secretory antibodies, or when unliganded, binds and excludes bacteria. Here we report the 2.6Å crystal structure of unliganded human SC (hSC) and comparisons with a 1.7Å structure of teleost fish SC (tSC), an early pIgR ancestor. The hSC structure comprises five immunoglobulin-like domains (D1-D5) arranged as a triangle, with an interface between ligand-binding domains D1 and D5. Electron paramagnetic resonance measurements confirmed the D1-D5 interface in solution and revealed that it breaks upon ligand binding. Together with binding studies of mutant and chimeric SCs, which revealed domain contributions to secretory antibody formation, these results provide detailed models for SC structure, address pIgR evolution, and demonstrate that SC uses multiple conformations to protect mammals from pathogens. A sticky substance called mucus lines our airways and gut, where it acts as a physical barrier to prevent bacteria and other microbes from entering the body. Mucus also contains proteins called antibodies that can bind to and neutralize molecules from microbes (known as antigens). The primary antibody found in mucus is called Immunoglobulin A. This antibody is produced by immune cells within the body and must pass through the “epithelial” cells that line the airway or gut to reach the layer of mucus. These epithelial cells have a receptor protein called the polymeric immunoglobulin receptor (plgR) that binds to Immunoglobulin A molecules, transports them across the cell, and then releases them into the mucus layer. The pIgR also releases Immunoglobulin A into breast milk, which protects nursing infants until their own immune system has developed. When released into the mucus layer, the Immunoglobulin A antibodies remain attached to a portion of pIgR known as the secretory component. This part of the receptor serves to stabilize and protect the antibodies from being degraded and helps the antibodies to bind to other host and bacterial proteins. Researchers have noted that the secretory component can be released into the mucus even when it is not attached to an antibody. These “free” secretory components have been shown to help prevent bacteria and the toxins they produce from entering the body. Despite the importance of secretory component in immune responses, the three-dimensional structure of the secretory component and how it interacts with antibodies and bacteria remained unknown. Here, Stadtmueller et al. use a technique called X-ray crystallography to determine a three-dimensional model of the free form of a secretory component from humans, and compare it to an ancestral secretory component protein found in fish. Further experiments on the human protein revealed how the structure of the secretory component changes when antibodies bind to it. Stadtmueller et al. propose a model for how both forms of the secretory component can protect the body from microbes and other external agents. The next challenge is to develop a three-dimensional model of the secretory component when it is bound to Immunoglobulin A.